Risiko Bencana Dalam Masyarakat Modern (International Forum of Researchers and Lecturers, 2023)
The risk society, also known as the Risk Society, is a term associated with the famous sociologist Ulrich Beck. According to him, we are still in a new era, even in a new form of modernity. There are still many sociological publications that still refer to the main idea of ​​a risk society. The concept of uncertainty follows a societal perspective that develops through a narrow perspective of the risk society regarding environmental hazards. The role of technology is often underexplained in sociological theory. So that technological risk is not taken into account in Beck's risk community concept. There are three basic characteristics that overlap from the first modernity in pursuing society of risk as an important concept. Disaster is an event or phenomenon that has the potential to cause damage resulting in loss of life and cause destruction of property. There are three types of disasters according to their causes. In risk research on sociological discourse, media and communication play a role in the construction of risks that get recognition about risks. Disaster management can be understood as a set of policies to make efforts related to disasters before, during and after a disaster, which include prevention, mitigation, preparedness, emergency response, healing and repair through appropriate and effective organizing activities. This can be criticized in two ways, namely, in terms of studies regarding the perspective of a socio-cultural approach to a risk and surveys regarding general risk awareness.